Human Resource Development Strategy In Improving Employee Performance Through Internal Communication As A Moderating Variabel - Rosita, Sry; Lestari, Asti Puji; Chairunnisa, Fitri (Finance and Business Management Journal, 2025)
The study aims to describe the general picture of employee performance, human resource development, and internal communication, test the influence of human resource development on employee performance, and test the influence of human resource development on employee performance through internal communication as a moderating variable at BPPRD Muaro Jambi Regency. The population and sample were 71 employees of BPPRD Muaro Jambi. Data collection was carried out by distributing questionnaires with a Likert scale. Data testing was carried out through outer model and inner model tests using SmartPLS 4.0. The results showed that employee performance (312.6), human resource development (299.6), and internal communication (307.5) at BPPRD Muaro Jambi were in the very high category. Human resource development has a positive and insignificant effect on employee performance and internal communication moderates the influence of human resource development on employee performance negatively and insignificantly. Therefore, it is recommended that BPPRD Muaro Jambi Regency from the aspect of employee performance needs to pay more attention to employee commitment, from the aspect of human resource development, development programs need to be further improved through non-training activities, and from the aspect of internal communication, social interaction needs to be further improved.